'I Do it My Way': The Meaning of Independence in Bandung Indie Musicians and Their Media Uses - Kelana Ashil Siddhawira; Dadang Sugiana (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Bandung from various discourses is often referred to as the epicenter of the development of popular culture in Indonesia, including the independent music scene. Along the way, being independent or mostly known as "indie" is increasingly popular and then has its own meaning for each musician who adopts and practices it. In addition, the role of the media in music activities is also inevitable. Whether it is  to maintain their relationships with audiences, share informations, or brand theirselves, they do it through the media. This research will provide a typification of how subjective meaning of being independent can be seen from the use and preferences of media by indie musicians. Researchers interviewed four musicians who live in Bandung. Each of the musicians was  interviewed at different times and places. The results show, there are three main types of indie musicians: The Idealists, The Moderates, and The Opportunists. Each type of indie musicians has their own characteristics regarding how they relate to the media. With this kind of typification, third parties (i.e governments, corporations, grassroots communities, etc) that  want to build mutual relationships with independent musicians in Bandung can be clearer about which musicians are most appropriate to meet their needs.